Optimalization of Formula and Compression Force on Texture and Dissolution Rate of Passion Fruits Effervescent Tablet - Ansar, Ansar (Jurnal Teknologi Pertanian, 2011)
The aims of this research were to determine influences of formula andcompression force on characteristic effervescent tablet of passion fruits. The researchwith treatment variation of six formula and five compression force. Variations of formulawere carried on by combining different ratio of citric acid and sodium bicarbonate (1:3,1:2, 1:1, 3:1, 2:1, and 2:3 w/w) and compression force of 1000, 2000, 3000, 4000, and5000 N. Characteristic of effervescent tablet of passion fruits that evaluated are textureand dissolution rate.The results of research showed that the compression force significantlyinfluenced (Î± > 0.05) on the texture and dissolution rate of effervescent tablet. Variationsof formula none significantly influenced (Î± < 0.05) on the texture and dissolution rate.The effervescent tablet of passion fruits of good characteristic is formula of ratio citricacid and sodium bicarbonate 1:2 w/w with compression force 3000 N.Keywords: formula, compression force, effervescent tablet